Exploring Applicability of Different Ecological Protection Measures for Soil and Water Loss Control of Highway Slope in the Permafrost Area: A Case Study of Qinghai-Tibet Highway in China - Xiaochun Qin; Anchen Ni; Dongxiao Yang; Bing Chen; Shiliang Liu (International Journal of Environmental Research and Public Health, 2023)
A variety of slope water and soil conservation measures have been taken along the Qinghai-Tibet Highway, but the systematic comparison of their erosion control ability needs to be strengthened, especially in the permafrost area. To explore the applicability of different measures to control runoff and sediment yield, field scouring experiments were conducted for different ecologically protected slopes, including turfing (strip, block, full), slope covering (gravel, coconut fiber blanket), and comprehensive measures (three-dimensional net seeding). Compared with the bare slope, the bulk density of the plots with the ecological protection measure decreased, the moisture-holding capacity and the organic matter increased correspondingly, and the average runoff velocity also decreased. The soil loss and runoff had a similar trend of different ecological protection measures. The relationship between the cumulative runoff and sediment yield of different measures exhibited a power function, with the increase of scouring flow and the runoff reduction benefit and sediment reduction benefit in different ecological protection-measured plots showing a decreasing trend. The average runoff reduction benefit decreased from 37.06% to 6.34%, and the average sediment reduction benefit decreased from 43.04% to 10.86%. The comprehensive protection measures had the greatest protection efficiency, followed by turfing, while the cover measure had limited improvement. Soil characteristics, vegetation coverage, and the scouring inflow rate are key factors that influence protection efficiency. The results suggest that comprehensive measures and turfing be taken rather than cover measures or bare slopes. This work provides an experimental reference for ecological protection methods for highway slopes in the permafrost area.